Ersatz für die Grundsteuer: eine einfache, effiziente, kostengünstige und gerechte Lösung - Gerhard Graf (Wirtschaftsdienst, 2018)
Die Einheitsbewertung des Grundvermögens für die Erhebung der Grundsteuer wurde im April 2018 vom Bundesverfassungsgericht als mit dem Grundrecht auf Gleichbehandlung nicht vereinbar befunden. Die Einheitsbewertung muss nun bis zum 31.12.2019 neu geregelt werden. Wird dies unterlassen, fällt die Grundsteuer ersatzlos weg. Da die Grundsteuer eine alleinige Einnahme der Kommunen ist, sind hier Proteste zu erwarten. Die Einnahmeausfälle könnten jedoch mit einer Beteiligung an der Umsatz- und Einkommensteuer kompensiert werden. – – The highest constitutional court in Germany recently declared that property tax is not in conformity with the constitution. A revision of the property tax laws needs to be undertaken but there is no consensus about a favourable solution yet. One of the main obstacles to a consensus is tackling the new assessments of over 35 million households and the ensuing wave of millions of lawsuits. This paper proposes avoiding those costs by slightly increasing the tax rates of the value added tax and income tax and giving the increased revenues to the municipalities as a substitute for the property tax. This procedure has at least two advantages: (1) It can take up and reflect the distributional effects of the property tax. (2) It is simple, efficient, economic and fair.
Keywords: H71; K34; R51; 330